The effects of corn starch addition on the freeze⁃thaw qualities of frozen rice noodles - YANG Wanying; WANG Ren; FENG Wei; WANG Tao; CHEN Zhengxing; ZHANG Hao (Shipin yu jixie, 2024)
ObjectiveThis study aimed to improve the high rate of broken rice noodles and serious muddy soup after flash freezing.MethodsThe effects of 20% corn starch addition on the cooking qualities, texture characteristics, sensory properties, freezable water content, moisture distribution and the surface microstructure of frozen rice noodles were investigated during the freeze⁃thaw treatment.ResultsThe addition of corn starch significantly improved the cooking quality of frozen rice noodles during the freeze⁃thaw cycle. The cooking loss and the breaking rate decreased by 42.31% and 36.97%, respectively, after 4 cycles of freeze⁃thaw treatment. Moreover, the contents of amylose and rice protein in the soup significantly decreased. After adding corn starch, the hardness and chewiness of frozen rice noodles increased by 22.97% and 26.57%, respectively, and the total sensory score increased by 13.04%. Meanwhile, corn starch addition inhibited the transition of deep⁃bound water to weak⁃bound water and decreased the content of freezable water, weakening the mechanical damage of frozen rice noodles by ice crystals, which enabled a smoother surface of frozen rice noodles than the control.ConclusionThe addition of 20% corn starch can improve the cooking quality and texture characteristics of frozen rice noodles, delay the deterioration of quality, inhibit the increase of internal water mobility and reduce the formation of ice crystals, thereby improving the freeze⁃thaw quality of frozen rice noodles.